EXTRACTION OF POLYSACCHARIDES AND TANNIN FROM SOME MEDICINAL PLANTS - Kim Dung, Vu; Quang Trung, Do; Van Viet, Nguyen (Journal of Forestry Science and Technology, 2017)
Medicinal plants such as Ganoderma lucidum (Leyss. Ex Fr.) Karst, Morinda officianalis How and Camellia tamdaoensis Ninh et Hakoda have been identified and used as medicinies to support human health. They were reported contain many chemical substances (like polysaccharides, tannins, and saponins) that can perform many biological functions, for example, defence against fungis, insects, and herbivoros mamals. However, the extraction of these bioactive subtances from medicinal plants is poorly understood. Of siginificance is optimization for the extraction of them from the medicinal plants, we extracted polysaccharide and tannin from Ganoderma lucidum (Leyss. Ex Fr.) Karst, Morinda officianalis How and Camellia tamdaoensis Ninh et Hakoda with the temperature from 70 - 900C in 30 - 90 minutes, and ratio of materials and solvent is from 1:25 to 1:100. The results showed that the optimized extraction condition of polysaccharide and tannin from Morinda officianalis How (water: ethanol = 1:1, solid material: liquid solvent = 1:25, at 100°C in 30 minutes); Camellia tamdaoensis Ninh et Hakoda (water: ethanol = 1:1, solid material: liquid solvent = 1:100, at 90oC in 30 minutes); Ganoderma lucidum (Leyss. Ex Fr.) Karst (water: ethanol = 1:2, solid material: liquid solvent = 1:75, at 100°C in 60 minutes). These results provide important insight regarding bioactive compounds from medicinal plants that may be useful for scientists in future.